Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Insertion professionnelle dans le domaine de la santé des personnes immigrantes francophones vivant en situation minoritaire - Forest, Mariève; Goss Gilroy Inc (Ministère Immigration, Réfugiés et Citoyenneté Canada, 2020)

Occupational Integration in Healthcare by French-speaking Immigrants Living in Minority Communities - Goss Gilroy Inc. (GGI) (2020)
This report presents the results of a research project on the occupational integration of French speaking immigrants in healthcare, in Francophone minority communities. Through interviews, this project examines the challenges faced by French-speaking immigrants working or pursuing a career in the health sector in Nova Scotia, Ontario and Alberta. Researchers also mobilized literature on the occupational integration of immigrants, data from the 2016 Census and the results of quantitative studies. The research shows that the need for English language skills constitutes a major obstacle at various stages of French-speaking immigrants’ occupational integration journey. The interviews also indicate that employment assistance services in French are not equipped to deal with the complex trajectories of internationally educated health professionals, or to help them identify alternative careers. During internships or at the start of employment, supports in French promoting the integration of immigrants (through mentoring, training workshops for employers, etc.) are very limited. Recommendations are addressed to the Department of Immigration, Refugees and Citizenship Canada and aim to improve supports offered to the study population from the start of their migration project to retention in their workplace.

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.